Management Analysis of the Implementation of Covid-19 Vaccination in Reducing Positivity Rate in Regency Health Office of Boyolali, Central Java - Aviandari, Tifa; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Health Policy and Management, 2021)
Background: The results of a vaccine acceptance survey conducted by the Ministry of Health together with the Indonesian Technical Advisory Group on Immunization (ITAGI) with the support of UNICEF and WHO in September 2020 showed that most people (74%) were aware of the government's plan to carry out COVID-19 vaccination. The government targets 181,500,000 Indonesians to receive the vaccine to achieve herd immunity. Through this vaccination effort, it is hoped that it will reduce the COVID-19 positivity rate. The positivity rate is the ratio between the number of positive cases of Covid-19 and the number of tests carried out. The purpose of this study was to qualitatively examine the management analysis of the implementation of Covid-19 vaccination in reducing positivity rate in Boyolali Regency Health Office.Subjects and Method: This was a type of descriptive research using a qualitative approach. Determination of informants is done by purposive sampling. Data was collected through indepth interviews, document review and observation. The data is processed through the stages of data reduction, data presentation and conclusion drawing and triangulation of sources and methods.Results:  The implementation of vaccination in the coverage area of the Boyolali Health Service was able to reduce the positivity rate in Boyolali. The COVID-19 vaccination procedure is carried out based on the requirements for the vaccine recipient community. According to the coordinator of the vaccination implementation at one of the hospitals in Boyolali (informant 1), they screened the patient's condition before starting the vaccination. In addition to screening medical history, vaccine participants must be confirmed to be in a negative condition or not suffering from COVID-19 disease. Data from the Boyolali Health Office shows that since the vaccine began (mid-February), the number of COVID-19 sufferers has decreased.Conclusion: The management of the Covid-19 vaccination implementation in the Boyolali Health Service coverage area was able to reduce the positivity rate in Boyolali Regency. After giving the vaccine, the number of positive Covid-19 patients is in the range of 10 to 20 cases per day.Keywords: vaccination, Covid-19, positivity rateCorrespondence: Tifa Aviandari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: aviandaritifa@gmail.com. Mobile: 089682108211Journal of Health Policy and Management (2021), 06(03): 190-202https://doi.org/10.26911/thejhpm.2021.06.03.04